Digital innovations of absolut factoring ltd as a guarantee of an enterprise’s competitiveness in modern conditions - O. V. Zinina; J. A. Olentsova (E-Management)
Innovative technologies emergence has changed the focus of new organizations development. In today’s realities, in order to take the lead in any given market, it is necessary to offer up-to-date ways of doing business and solving problems. This rule applies to both the largest and established organizations and emerging ones, whose main task is to ensure a favorable start and a significant advantage over big competitors. The study is relevant because digital innovation has not yet as well developed in the Russian domestic market in certain areas. For this reason, even the simplest innovation that accelerates any important processes will serve as a huge lever to manage the market situation. When introducing a completely new technology, large competitors will not be able to provide the same stability, speed, or reliability, despite the amount of funds available. The key objective of the research is to develop a digital innovation that can improve competitiveness and efficiency of a selected organization with a particular specificity. Its outcome can be development and an example of implementing an effective tool that will enable factoring companies to grow their business and provide SMEs with access to finance.